A Comparison of the Efficacy Between Mass Closure and Layer by Layer Closure of Midline Laparotomy and Its Influence on Wound Healing: A Prospective Study - Kidwai, Roman; Sharma, Anup (Journal of Nepalgunj Medical College, 2024)
Introduction: The midline laparotomy is the most common approach in surgery which gives access to viscera of the abdomen. Following surgery, the laparotomy wound is sutured by two techniques: mass closure and layer by layer closure. The primary objective of wound closure is to restore the function of the abdominal wall. However the method adopted for incision closure has an influence on the outcomes of wound healing. Our study wants to compare the two suture techniques in terms of efficacy and wound healing. Aims: To compare conventional layer by layer suture technique versus mass closure in terms of efficacy and wound healing in patients with midline laparotomy approach. Methods: A Prospective study with a population size of 94 was performed at the surgery department of Nepalgunj medical college teaching hospital, Nepalgunj, starting from September 2023 to May 2024. A pre-tested questionnaire containing structural, semi-structural, and open-ended questions in printed form was made as a data collection tool. All the people in this study were interviewed after receiving their consent. Patients were followed up for 3 months to rule out any post operative complications. Results: Total 94 patients were studied among which majority of patients were in 30-39 age group. Male outnumbered the females. Incidence of early complications like seroma, wound infection and wound dehiscence was more in layered closure group as compared to mass closure. Average time taken in layered vs. mass closure group is 15 vs 25 mins respectively. Overall wound healing was found more efficacious in mass closure group which is also cost effective than layered closure group. Conclusion: Mass closure technique is less time consuming, along fewer instances of surgical site infection and dehiscence with better overall compliance.